MENINGKATKAN HASIL BELAJAR TEMATIK TEMA 1 INDAHNYA KEBERSAMAAN MELALUI MODEL PEMBELAJARAN INSIDE-OUTSIDE-CIRCLE DI KELAS IV SD NEGERI 91 KENDARI SEMESTER 1 TAHUN PELAJARAN 2022/2023 - Ambo Lallo Dg Paliwang (CV. ADIBA AISHA AMIRA, 2023)
Learning thematic theme 1 the beauty of togetherness for some students might be considered difficult. In connection with this, in semester I, students experienced a decline in learning outcomes. The low student learning outcomes have been proven by the acquisition of pre-test results on theme 1, the beauty of togetherness from 18 Class IV students at SD Negeri 91 Kendari. Based on the results of the students' pre-test, 6 students or 33.33% of the classical completeness scores were successful in achieving the KKM score. And students who have not reached the classical mastery target are 12 students or 66.66%. The KKM score is 70. Seeing this statement, it can be said that the problem above is the author is interested in researching and testing the extent to which mathematics learning outcomes in the material of sine and cosine rules through the inside-outside-circle learning model. This research method uses class action research methods (Classroom Action Research). This classroom action research was conducted at SD Negeri 91 Kendari Class IV. The research was conducted from July 2019 to September 2021. The research subjects were Class IV students at SD Negeri 91 Kendari for the 2022/2023 academic year. There are 18 students in Class IV. Data collection techniques in this study are observation, interview and documentation methods. In the pre-cycle, the classical student learning outcomes were 33.33% in the